ANALYSIS AND DESIGN OF A MEDICAL RECORD DATA MANAGEMENT INFORMATION SYSTEM WITH A HUMAN CENTERED DESIGN APPROACH - Aldi Subari; Andi Zulherry (Tsabit Journal of Computer Science, 2025)
Klinik Medika Al-Azhar still uses a manual medical record system that causes various operational constraints such as lost files, delays in patient data retrieval, and the absence of real-time medication stock monitoring. This research aims to analyze and design a web-based Medical Record Data Management Information System using a Human Centered Design (HCD) approach to improve data management efficiency at Klinik Medika Al-Azhar. The research employs a descriptive qualitative method with HCD stages including empathize, define, ideate, prototype, and test. Data collection was conducted through interviews, observations, document analysis, and prototype testing. The system was built using PHP and MySQL with interface design using Figma. Testing was performed using the Blackbox Testing method. The designed system successfully meets user needs in inputting, managing, and searching medical record data quickly and accurately. System implementation is capable of generating automatic medical record reports, reducing the risk of data loss, and improving the quality of clinic services. Blackbox testing results show that all system functions run properly. The HCD approach proved effective in producing an information system that aligns with user needs and preferences, improves data processing efficiency, and supports the enhancement of healthcare services.